Interactive effects of hydrogen sulphide and silicon enhance drought and heat tolerance by modulating hormones, antioxidant defence enzymes and redox status in barley (Hordeum vulgare L.). (8th December 2021) - Naz, R.; Gul, F.; Zahoor, S.; Nosheen, A.; Yasmin, H.; Keyani, R.; Shahid, M.; Hassan, M. N.; Siddiqui, M. H.; Batool, S.; Anwar, Z.; Ali, N.; et al.
Abstract: Recent changes in climate have reduced crop productivity throughout much of the world. Drought and heat stress, particularly in arid and semi‐arid regions, have seriously affected barley production. This study explored the separate and interactive effects of silicon (Si) and hydrogen sulphide (H2 S) on plant growth and mitigation of the adverse effects of heat stress (DS) and drought stress (HS) in a barley pot experiment. The impacts of simultaneous DS + HS were more severe than individual stresses due to increased ROS production, malondialdehyde (MDA) content and higher electrolyte leakage (EL), thereby leading to reduced water, protein and photosynthetic pigment content. Exogenously applied Si and H2 S alleviated the DS‐, HS‐ and DS + HS‐induced effects on barley by reducing ROS production, MDA and EL. A single application of H2 S or Si + H2 S increased plant biomass under all stress conditions, which can be ascribed to higher Si accumulation in barley shoots. A single application of Si or H2 S significantly increased plant biomass. However, Si + H2 S was the most effective treatment for metabolite accumulation and elevating activity of antioxidant enzymes to prevent toxicity from oxidative stress. This treatment also modulated osmolyte content, enhanced antioxidant activity and regulated the stress signalling‐related endogenous hormones, abscisic acid (ABA) and indole acetic acid (IAA). Exogenous treatments regulated endogenous H2 S and Si and resulted in higher tolerance to individual and combined drought and heat stress in barley. Abstract : Silicon affects leaf H2 S levels and both interactively enhance drought and heat stress tolerance in barley by modifying oxidative indicators, tolerance‐related antioxidant enzymes and endogenous hormones.